Foreign Bank Participation and Crises in Developing Countries - Cull, Robert (World Bank, Washington, DC, 2012)
This paper describes the recent trends in foreign bank ownership in developing countries, summarizes the existing evidence on the causes and implications of foreign bank presence, and reexamines the link between banking crises and foreign bank participation. Using data on the share of banking sector assets held by foreign banks in over 100 developing countries during 1995-2002, the results show that countries that experienced a banking crisis tended to have higher levels of foreign bank participation than those that did not. Furthermore, panel regressions indicate that foreign participation increased as a result of crises rather than prior to them. However, post-crisis increases in foreign participation did not coincide with increased credit to the private sector, perhaps because in many cases foreign banks acquired distressed banks.